Management of BKK During the Covid-19 Pandemic as an Effort For Graduate Appliance - Anti, Pridianti Dian; Sunandar, Asep; Sunarni, Sunarni (Universitas Negeri Malang, 2021)
Abstract: This study aims to describe (1) the policies in planning, implementing, and supervising the special job, (2) Strategies and cooperation implemented by the special job fair with work partners, and (3) the usefulness of special job fair in developing the carrier of SMK Negeri 4 Malang students. The research method used is a qualitative research method using a case study design. Data collection techniques used are interviews, documentation, and observation. The subjects of this research are the chairman of a special job fair, member of a special job fair, head of public relations, admin of public relations, three students, and three graduates. Data analysis is used with data reduction, data presentation, and conclusion drawing or verification. The results of this study are, (1) The supervision of BKK activities was conducted directly and indirectly by Public relations. BKK evaluated and reported the result of graduate search result viii and the report of work program to internal and external schools; (2) Strategies and cooperation implemented by the special job fair with work partners in Covid-19 Pandemic were done by applying two approaches namely BKK targeting or aiming the industries or the industries requesting to cooperate with BKK, and (3) The usefulness of the special job fair in developing the carrier of SMKN 4 Malang students was done through educative webinar implementation during Covid-19 Pandemic is increasing their knowledge and preparation to continue the next carrier they desire, through working, building a business, or continuing their study. Keywords: The management of special job fair, Covid-19 pandemic, a workforce of the vocational school graduates, role in public relations and partnership, the world of business and industry